Dysautonomia in prodromal α‐synucleinopathy: peripheral versus central autonomic degeneration. (4th February 2016) - Dahms, C.; Guenther, A.; Schwab, M.; Schultze, T.; Nowack, S.; Hoyer, D.; Ehrhardt, J.; Witte, O. W.; Mayer, G.; Rupprecht, S.
Abstract : Background and purpose: There is an urgent need for early predictive markers for the course of disease in prodromal α‐synucleinopathies such as idiopathic rapid eye movement (REM) sleep behaviour disorder. Autonomic cardiac/vascular dysfunction is a prominent feature in advanced α‐synucleinopathies, but its diagnostic value as an early neurodegenerative marker remains unclear. The latter may be complicated since synuclein‐mediated neurodegeneration may involve central and peripheral components of the autonomic nervous system. Methods: The diagnostic value of autonomic symptoms and central and peripheral autonomic markers of blood pressure and heart rate regulation were prospectively evaluated in 20 subjects with idiopathic REM sleep behaviour disorder and 20 age‐matched healthy controls. Results: Although subjects with REM sleep behaviour disorder showed no clinical autonomic symptoms, blood pressure ( P ≤ 0.035) and heart rate response ( P ≤ 0.065) were slightly diminished during orthostatic challenge. Autonomic dysregulation was distinctively reflected in lower resting heart rate (all components, P ≤ 0.05) and blood pressure variability (low frequency component, P ≤ 0.024) indicating peripheral cardiac/vascular denervation. In contrast, baroreflex sensitivity and central cardiac autonomic outflow (sympathovagal balance) were well preserved indicating intact central autonomic regulation. Heart rate variability [very low frequency component, receiver operating characteristic (ROC) area under the curve (AUC) 0.80, P ≤ 0.001] and blood pressure variability (low frequency component ROC AUC 0.73, P ≤ 0.01) but not baroreflex sensitivity and sympathovagal balance showed an excellent diagnostic accuracy in identifying subjects with REM sleep behaviour disorder and healthy controls. Conclusions: Cardiac/vascular dysfunction in prodromal α‐synucleinopathy arises from peripheral rather than from central autonomic degeneration. Autonomic indices encoded in heart rate and blood pressure variability are precise functional markers of early synuclein‐mediated neurodegeneration.